New methods for analyzing the hybrid zone of our fire-bellied toads (genus Bombina) - Straková, Helena (Jihočeská univerzita, 2010)
In this elaborate the methods that are used for studying the hybrid zone of Bombina bombina and B. variegata were summarized. The principals, advantages and disadvantages of these methods are mentioned.
New methods for analyzing the hybrid zone of our fire-bellied toads (genus Bombina)
Keywords: Bombina; variegata; hybrid zone; morphometry; morphology; method; allozymes; SSCP; microsatellites; mtDNA; fire-bellied toads